2017
DOI: 10.1371/journal.pone.0180707
|View full text |Cite
|
Sign up to set email alerts
|

Yield of community-based tuberculosis targeted testing and treatment in foreign-born populations in the United States: A systematic review

Abstract: ObjectiveTo synthesize outputs and outcomes of community-based tuberculosis targeted testing and treatment (TTT) programs in foreign-born populations (FBP) in the United States (US).MethodsWe systematically searched five bibliographic databases and other key resources. Two reviewers independently applied eligibility criteria to screen citations and extracted data from included studies. We excluded studies that contained <50% FBP participants or that examined steps only after diagnosis of latent TB infection (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…While no information is currently available on potential risk of occurrence of antibiotic-resistant strains of Mycobacterium tuberculosis in the communities adjacent to hog CAFOs, this aspect may require detailed analysis. The increased risk of undiagnosed latent tuberculosis that may be present in these communities, which may have a higher number of foreignborn residents [45], also requires attention. Co-existence of factors that may promote tuberculosis from its latent to active form (eg, diabetes, immunosuppression, and other conditions) needs to be accounted for when developing a strategy for improving identification of latent and active cases (ie, through screening) and treatment adherence in patients who require therapy.…”
Section: Locations Of Matched Nc Zip Codes Without Hog Cafos (Matchedmentioning
confidence: 99%
“…While no information is currently available on potential risk of occurrence of antibiotic-resistant strains of Mycobacterium tuberculosis in the communities adjacent to hog CAFOs, this aspect may require detailed analysis. The increased risk of undiagnosed latent tuberculosis that may be present in these communities, which may have a higher number of foreignborn residents [45], also requires attention. Co-existence of factors that may promote tuberculosis from its latent to active form (eg, diabetes, immunosuppression, and other conditions) needs to be accounted for when developing a strategy for improving identification of latent and active cases (ie, through screening) and treatment adherence in patients who require therapy.…”
Section: Locations Of Matched Nc Zip Codes Without Hog Cafos (Matchedmentioning
confidence: 99%
“…In our previous work, we examined the yield of community-based testing programs targeting foreign-born persons who were not known to be contacts of infectious TB cases [ 7 ]. In that work, we found that, for every 100 persons targeted in PFB groups, 40 had valid test results, 16 tested positive, and 5 completed LTBI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, while there are only a few thousand cases of active TB per year in the US, there are millions of persons with LTBI living in the United States, most of whom were infected abroad. Contact investigations alone clearly cannot be relied upon to reach the majority of at-risk foreign-born persons, and must be supplemented with other targeted testing activities, such as community-based targeted testing programs and pre-arrival testing and treatment of US-bound immigrants [ 7 , 29 ], if sustained declines in tuberculosis incidence and prevalence are to be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations